2016
DOI: 10.1002/jmri.25189
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative BOLD imaging at 3T: Temporal changes in hepatocellular carcinoma and fibrosis following oxygen challenge

Abstract: PurposeTo evaluate the utility of oxygen challenge and report on temporal changes in blood oxygenation level‐dependent (BOLD) contrast in normal liver, hepatocellular carcinoma (HCC) and background fibrosis.Materials and MethodsEleven volunteers (nine male and two female, mean age 33.5, range 27–41 years) and 10 patients (nine male and one female, mean age 68.9, range 56–87 years) with hepatocellular carcinoma on a background of diffuse liver disease were recruited. Imaging was performed on a 3T system using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Several preliminary studies have already shown the use of hyperoxic gas challenge to stimulate BOLD and/or TOLD MRI signal responses in tumors at distinct disease sites (breast [56, 57], cervix [49, 58, 59], brain [38, 60], prostate [61], and liver [62]). Breathing oxygen is particularly appropriate, since this is standard intervention in emergency medicine and thus it is quite straightforward to gain IRB approval.…”
Section: Discussionmentioning
confidence: 99%
“…Several preliminary studies have already shown the use of hyperoxic gas challenge to stimulate BOLD and/or TOLD MRI signal responses in tumors at distinct disease sites (breast [56, 57], cervix [49, 58, 59], brain [38, 60], prostate [61], and liver [62]). Breathing oxygen is particularly appropriate, since this is standard intervention in emergency medicine and thus it is quite straightforward to gain IRB approval.…”
Section: Discussionmentioning
confidence: 99%
“…18 In humans, gas challenges have been used to elicit T * 2 signal changes in studying hepatocellular carcinoma. 24,32 This study had limitations for the gas challenge. The main drawback of a hypercapnic challenge is the patient tolerability of the inspired CO 2 , which limits the level of P ET CO 2 , resulting in a smaller change in liver hemodynamics compared with the animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Profound changes to liver tissue composition may exist in certain hepatic diseases. While the oxygen‐enhanced hepatic BOLD approach eliminates confounding factors from liver tissue composition, the measurement is still sensitive to variations in the liver hemodynamic response to hyperoxia in different diseases …”
Section: Discussionmentioning
confidence: 99%
“…For example, in healthy controls with intact vascular autoregulatory mechanisms, an oxygen‐challenge induces negligible changes to liver R 2 * , because breathing pure oxygen causes no changes to hepatic blood flow and hepatic tissue oxygenation . In patients with liver fibrosis and HCC, significant but variable responses have been observed . Therefore, oxygen‐enhanced hepatic BOLD is highly dependent on the hepatic vascular response and may not be able to accurately assess tissue oxygenation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation